Comparison of students' perception towards the effectiveness, early reaction, and acceptance of knowledge and skills during the 'Skuad Jelajah Motivasi Pendidikan dan Kepenggunaan' programme - Che Jusoh, Othman; Sabri, Mohamad Fazli; Ismail, Ismi Arif; Suandi, Turiman (Zes Rokman Resources, 2017)
The ‘Skuad Jelajah Motivasi Pendidikan dan Kepenggunaan’ programme is considered as a response programme towards the increment of issues in consumerism among teenagers and youth, as well as a programme intended for giving motivation and knowledge of consumerism to form five students at Malaysian Secondary Schools in the Peninsular of Malaysia (“Dedah pelajar mengenai,” 2014). During its implementation, an evaluation was concurrently carried out at the end of the programme in order to improve its implementation in the future. In order to evaluate the programme, three aspects were given the emphasis, of which, the overall perception of effectiveness among students, their early reactions, and their acceptance of knowledge and skills of consumerism using the Kirkpatrick (1994) model of programme evaluation. A cross-sectional survey design was implemented for the purpose of the evaluation. A total number of 7,840 form five students were asked to answer the student’s perception scale towards the effectiveness of Consumerism Programme. The MANOVA test revealed that there are significant differences of mean score for the three independent variables (overall perception of students, their early reactions, and their acceptance of knowledge and skills of consumerism) according to gender; F(2, 6845)=109.80, p<.05; Pillai’s trace=.98; partial eta squared=.031. Female respondents (M=3.85, SD=.53) scored higher than their counterparts (M=3.66, SD=.56) in the overall perception of effectiveness, female respondents (M=3.74, SD=.62) scored higher than their counterparts (M=3.55, SD=.66) in early reaction, and female respondents (M=3.90, SD=.59) scored higher than their counterparts (M=3.72, SD=.63) in their acceptance of knowledge and skills of consumerism. Overall, the effectiveness of ‘Skuad Jelajah Motivasi Pendidikan dan Kepenggunaan’ programme is rated moderate by the female students, surpassing the male students. In specific, the programme was able to moderately improve the level of early reaction and acceptance of knowledge and skills towards the aspects of consumerism among form five students at the secondary schools in the Peninsular Malaysia. It is hoped that the findings of this study could act as a point of reference in improving the organizational culture of KPDNKK and GPMS, especially on the aspects of programme planning, implementation, and personnel training in the future as well as filling up the significant gap in the literature on consumer programme evaluation in Malaysia.